Medicinal Application of Native Plants (Lamiaceae and Rosaceae Family) in Alamut Region in Gazvin Province - M Ahvazi; V Mozaffarian; T Nejadsatari; F Mojab; MM Charkhchiyan; F Khalighi-Sigaroodi; Y Ajani (Institue of Medicinal Plants, ACECR, 2007)
Background: Considering the fact that traditional knowledge forms the basis for development of new natural products in the other hands the elder people in some villages possess the traditional knowledge and with death of them, this knowledge is rapidly eroding. So it is an urgent necessity to record and conserving as quickly as possible all information about plants. Objective: Consideration and study of connections between usage and cultures believes about medicinal plants (Ethnobotany) is interesting and important basis for research. The aim of this research was studied of two family (Lamiaceae and Rosaceae) in some Alamut villages to know how the people use of these plants for their treatment. Methods: The investigated area was divided into different villages with the help of map. Questionnaires were used and devised to identify and document the traditional knowledge of local people. Information and data on various aspects of the plants such as traditional uses, and collection method and time of each species in the area were gathered from the local experienced persons through interviews and discussions. The plants were gathered from different altitude and sites. Then the fully dried specimens were mounted on herbarium sheets. A set of voucher specimens were deposited to IMPH. Results: In this investigation 11 medicinal species of Lamiaceae and 10 medicinal species of Rosaceae family were found that used frequently by native people. Conclusion: In this region there are some rare plants that can be subjected for investigations by researcher for their effects that may be interesting for their therapeutic effects.